Work Interruption Experienced by Nurses during Medication Administration Process and Associated Factors, Northwest Ethiopia - Mehammed Adem Getnet; Berhanu Boru Bifftu (Nursing Research and Practice)
Background. During medication administration process, including preparation, administration, and documentation, there is high proportion of work interruption that results in medication administration errors that consequently affect the safety of patients. Thus, the main purpose of this study was to assess the prevalence of work interruption and associated factors during medication administration process. Methods. A prospective, observation-based, cross-sectional study was conducted on 278 nurses. Structure observational sheet was utilized to collect data. EPI Info version 3.5.3 and SPSS version 20 software were utilized for data entry and analysis, respectively. Binary and multivariable logistic regression were fitted to identify the associated factors using an odds ratio and 95% CI. Results. The incidence of work interruption was found to be 1,152 during medication administration process. Of this, 579 (50.3%) were major/severe work interruptions. Unit of work, day of the week, professional experience, perceived severity of work interruption, source/initiator of interruption, and secondary tasks were factors significantly associated with major work interruptions at p<0.05. Conclusion. In this study, more than half of work interruption was major/severe. Thus, the authors suggest raising the awareness of nurses regarding the severity of work interruptions, with special attention to those who have lower work experience, sources of interruption, and secondary tasks by assigning additional nurses who manage secondary tasks and supportive supervision.